Bilateral investment treaties and sovereign default risk - Stefan Eichler; Jannik A. Nauerth (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2021)
This paper analyzes the impact of bilateral investment treaties (BITs) on sovereign bond returns of 25 emerging markets from 1993 to 2016. Under a BIT, foreign investors can use an international arbitration scheme to enforce compensation claims against the domestic government in case of direct or indirect expropriation. We focus on the so far unexplored effects of legal risk associated with BITs on sovereign creditworthiness. We find small unconditional effects of BITs on sovereign bond returns. Taking the heterogeneity of BITs and political regimes into account, we find robust and strong negative effects. In countries with high political risk of expropriation (measured by low executive constraints), we find that the implementation of investor-friendly BITs is associated with a significantly negative impact on sovereign bond returns, accounting for roughly 15% of bond returns' standard deviation.
urn:nbn:de:bsz:14-qucosa2-752674
Keywords: G15; G12; F30; K33; 330; Sovereign default risk; Bilateral investment treaty; Political risk; Legal risk; Emerging markets